JOB SATISFACTION AND EMPLOYEE ENGAGEMENT FOR EMPLOYEES PERFORMANCE - ahmad rabbani; ra afera ratna wijayanti; joni gusmali; achmad zulfiqo irwan (IULI Publisher, 2023)
Facing competition in today’s free market, every company will try as optimally as possible to maintain its assets. Employees as human resources are one of the factors that cannot be duplicated or imitated by competitors and are considered the most valuable assets if managed and involved properly. One way to manage and maintain the main human resources today is to focus on organizational performance through evaluating the employee’s job satisfaction and employee engagement. This research aims to analyze the influence of job satisfaction and employee engagement on organizational performance. This research is using quantitative data in form of questionnaires were distributed to 54 employees who works in PT. Aero Wisata. Structural Equation Modeling (SEM) was applied to produce path diagram, regression weights and model fit to analyze the research model. Result found that job satisfaction has a positive influence significantly on organizational performance by 39%. But employee engagement has a positive but not significantly influence on organizational performance by 30%. Based on the result, PT. Aero Wisata is suggested to carry out further identification related to job evaluations and sincrease collaboration between departments in order to create harmony that supports the direction and setting goals of the company Keyword: Job Satisfaction, Employee Engagement, Organizational Performance